SYSTEMATIC LITERATURE REVIEW: IMPLEMENTASI ARTIFICIAL INTELLIGENCE DAN MACHINE LEARNING PADA BIDANG AKUNTANSI MANAJEMEN - Muhammad Akmaluddin; Totok Dewayanto (Diponegoro Journal of Accounting, 2023)
This research aims to identify the implementation of artificial intelligence and machine learning in the field of management accounting based on published research articles. Additionally, this study aims to explore gaps in knowledge to contribute to future academic studies. A systematic literature review (SLR) method was employed to analyze various articles published in academic journals indexed in Scopus from 2018 to 2023. Articles were screened using predefined keywords obtained from top-ranked journals. The SLR method was used to review the topics/themes, findings, methodologies, recommendations, and limitations of the published articles. The analysis results provide evidence that the implementation of artificial intelligence and machine learning in management accounting enhances the effectiveness and efficiency of management accountants. It is important to encourage the adoption of this technology to unlock its significant potential, while also considering the ethical aspects of its implementation. This research is expected to be beneficial and contribute to future research development by providing insights and identifying research gaps in the implementation of artificial intelligence and machine learning in management accounting.